Silica Core-shell Formation of Nanophosphors - Kotov, Dmytro; Cho, So-Hye; Thuy, Duong Thi Dinh; Koval, Viktoriia (2017 IEEE 37TH INTERNATIONAL CONFERENCE ON ELECTRONICS AND NANOTECHNOLOGY (ELNANO), 2017)
Fabrication of core/shell-structured Y2O3:Bi, Eu/SiO2 nanophosphors was presented. The core nanophosphors, Y2O3:Bi,Eu, were synthesized by urea precipitation and annealing. The silica shell was formed by modified Stober method and its thickness was controlled by the amount of TEOS. Additional heat-treatment was applied on the core-shell particles in order to remove any residual impurities. Size and shape of core and core/shell particles were investigated by SEM analysis.